2016
DOI: 10.1002/polb.24274
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional instabilities of polyester and polyolefin films as origin of delamination in laminated multilayer

Abstract: Polymer-metal multilayer films provide attractive barrier properties to air and water, provided by several films bonded together. Used in high temperature and humidity, the delamination is the most common degradation mechanism. This mode of failure is critical because it leads to premature loss of barrier properties. Therefore, delaminations limit the use of multilayer in these conditions. Delamination should result from interfacial shear stress, and plausibly from difference of shrinkage of the films, due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The delamination in this polyolefin–polyester interface is strongly related to the shrinkage of the PP film. Indeed, a heat treatment of this film at 70°C during 192 days can induce a noticeable shrinkage of approximately −0.7% (Dubelley et al, 2017a). These authors showed that for such a shrinkage level, the PET/PU/PP interface was delaminated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The delamination in this polyolefin–polyester interface is strongly related to the shrinkage of the PP film. Indeed, a heat treatment of this film at 70°C during 192 days can induce a noticeable shrinkage of approximately −0.7% (Dubelley et al, 2017a). These authors showed that for such a shrinkage level, the PET/PU/PP interface was delaminated.…”
Section: Resultsmentioning
confidence: 99%
“…For example, delaminations of the PU adhesive layer at PET-Al/PU/PET-Al interfaces have been observed after only 1.5 years of aging at 65°C/75% RH (Brunner and Simmler, 2008). Other authors even evidenced debonding between PET and the sealing interface after 48 and 96 days of aging at 70°C/90% RH, respectively for PE and PP sealant materials (Garnier et al, 2011; Dubelley et al, 2017a). …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation